Assessing the waste management practices of tourist accommodation in polonnaruwa - Lankeshwara, L.S.R; Devaisy, S. (University of Jaffna, 2020)
The natural splendour, tropical weather, and historical sites of the island attracts tourists from all over the world. the contribution of tourism industry is vital to the countrys economy. since the tourism is a fast-growing industry, the increasing number of tourist visiting Sri Lanka resulted to increased number of tourists accommodations. The improper management of waste in the tourist accommodations becomes challenging in its ensuring environmental and human health. The Polonnaruwa district is a city and one of the World heritages sites, attracts international as well as domestic tourism. The study area is facilitated with different grades of accommodations for tourists, however, there is no studies undertaken with regard to waste management practices in the tourist accommodations in the Polonnaruwa district. Therefore, the objective of this study was to assess the existing waste management practices undertaken by the tourist accommodation (registered in Sri Lanka Tourism Development Authority (SLTDA)) in Polonnaruwa district where Thamankaduwa urban area was focused as it has more tourist accommodations. The type of the accommodation was categorized type A (basic) to type E (Luxury) based on the facilities available for accommodation. The date collected (n= 40) randomly through structured questionnaires, personal interviews and visual observations. The data were analysed using MS Excel platform and SPSS statistical software. Based on the results,Accommodation type "E" was the highest waste generator (31.4%) whilst "A" was the last (7.3%)further, type "E" was the highly adopted environmentally friendly precties for waste managment as recycle and reuse than type "A" accommodation , type "E" converted more organic wastes/garden wastes to compost and glass and rubber waste for recycling purposes than type "A" accommodation. in terms of onsite wast managment officials of type "E" accommodation were highly sipportive compared to the same type "A" beceause the official may have better knowledge/awareness regarding onsite waste management. However, some of the managers are reluctant in adopting onsite waste management practices due to lack of knowledge and space limitations
Keywords: : tourist; accommodation; solid; waste; management